Stop‐Flow Pelvic Chemoperfusion for the Treatment of Malignant Pelvic Bone Tumors: A Preliminary Study - Wang, Han (Orthop Surg, 2020)
OBJECTIVE: To preliminarily study the efficacy and safety of stop‐flow pelvic chemoperfusion, a novel therapeutic strategy for treating pelvic malignancies. METHODS: Stop‐flow chemoperfusion was performed six times in 5 patients with primary pelvic malignancies. Aortic and vena cave balloons and tourniquets were used to isolate pelvic blood flow from systemic circulation. Cisplatin was then perfused through a transarterial catheter to achieve exposure to a higher drug concentration. Pelvic and peripheral blood samples were collected to determine drug concentration during perfusion. The efficacy of stop‐flow pelvic perfusion was assessed by measuring the change in tumor size, the visual analogue scale, and the tumor necrosis rate after perfusion. Safety was assessed by classifying adverse events according to CTCAE v4.03. RESULTS: The mean area under the curve (AUC) and maximum drug concentration in the pelvis during perfusion were 246.23 min μg/mL and 17.29 μg/mL, respectively. These measures were significantly higher than the peripheral mean AUC and maximum drug concentration of 52.08 min μg/mL and 5.14 μg/mL, respectively. All 5 patients showed stable disease in response, with changes in tumor size of −4.7%, −5.4%, +4.7%, −8.4%, and 0.0%. Among the 5 patients, 3 (60%) experienced significant pain relief after perfusion. Three patients underwent surgery, with tumor necrosis of 63%, <60%, and 93%. No severe complications were observed in this study. CONCLUSIONS: Stop‐flow pelvic chemoperfusion resulted in exposure to drug higher concentration with fewer serious complications. These preliminary results suggest that further studies are required to comprehensively assess the therapeutic potential of stop‐flow pelvic chemoperfusion in pelvic malignancies.